Histopathological Features of Facet Osteoarthritis in Patients with Lumbar Spinal Stenosis. Issue 1 (April 2016) - Netzer, Cordula; Urech, Karin; Huegle, Thomas; Benz, Robyn Melanie; Hirschmann, Anna; Geurts, Jeroen; Schaeren, Stefan
Introduction: Lumbar spinal stenosis (LSS) is a degenerative, age-related narrowing of the lower spinal canal that causes pressure on the nerves, leading to pain and reduced mobility. Hypertrophy of ligament flava and facet joints combined with disc protrusions are a causative for LSS. Osteoarthritic changes to the facet joint, including joint space narrowing, subchondral cysts and osteophyte formation are commonly detected using magnetic resonance imaging (MRI) and computed tomography (CT) scanning. However, the pathomechanisms of facet joint osteoarthritis (OA) at a cellular and molecular level are poorly understood and have been scarcely studied. In this study we sought to investigate the histological features and to uncover cellular pathomechanisms of facet joint OA. Material and Methods: Fifteen patients undergoing surgical decompression due to degenerative LSS were included in this study (9 female/6 male, median age 66, range 49–85). Routine preoperative X-ray and MRI scanning of the lumbar spine was performed in all subjects. Severity of facet joint OA was assessed in MRI images using the Weishaupt grading system for the lumbar spine. The medial portion of facet joints was collected during surgical decompression of the spinal canal and processed for tissue histology. Tissue morphology was evaluated using haematoxylin and eosin (HE), Safranin-O and van Gieson's stains. The presence of macrophages, blood vessels and nerve fibers was investigated using immunohistological staining for their respective markers CD68, CD34 and PGP9.5. Functional osteoclasts were visualized using tartrate-resistant acid phosphatase (TRAP) staining. Subchondral bone area fraction (B.Ar/T.Ar) was determined using the ImageJ-plugin BoneJ. Results: OA was evident in MRI images characterized by joint space narrowing, bone edema and cysts and hypertrophy of articular processes. The severe OA phenotype in facet joints from LSS patients was confirmed at a histological level by complete loss of proteoglycan staining, CD34+ vessel penetration, and fissuring of cartilage tissue. Subchondral B.Ar/T.Ar ranged between 0.6 and 0.8. In all samples, subchondral marrow spaces contained CD34+ blood vessels and CD68+ mononuclear macrophages. CD68+ multinucleated osteoclasts were detected in resorption pits at the bone surface in 80 percent of the patients. Functionality of osteoclasts was confirmed by positive staining of multinucleated bone cells for TRAP in serial sections. Osteoblast activity was demonstrated in 60 percent of the patients and predominantly characterized by large areas of intramembranous bone formation near the osteochondral junction. Formation of an osteoclast-rich pannus-like tissue was seen in one sample. Innervation of subchondral marrow spaces by PGP9.5-positive nerve fibers was scarce and exclusively found in the vicinity of arterioles. Conclusion: Facet joints in LSS patients display radiological and histopathological features of OA. Two major OA phenotypes can be distinguished based upon cellular pathomechanisms in subchondral bone tissue: 1) osteoblast-rich intramembranous bone formation and 2) osteoclast/macrophage rich remodeling. Osteoimmunological mechanisms, specifically the interaction of CD68+ macrophages with bone-resident cells, play a – previously unknown – role in regulating subchondral bone sclerosis in progressive osteoarthritis. Targeting osteoimmunology might hold potential as a disease-modifying treatment for osteoarthritis.